Equilíbrio entre trabalho e vida pessoal de teletrabalhadores brasileiros - Rocha, Fabiana dos Santos (Universidade Federal de São Carlos, 2023)
Work-life balance is gaining increasing attention around the world, considering its impact on workers’ health and on organizational outcomes. Although there is extensive research on work-family balance, it is important to use a broader definition of personal life in order to include workers with a wider range of life trajectories, contributing to a better balance between work and non-work for all those in the workforce. Furthermore, research evidence is needed to identify factors that affect perceptions of work-life balance among the growing number of people who are teleworkers. Thus, the overall objective of this thesis was to expand our understanding of work-life balance among Brazilian teleworkers. This objective was addressed through three studies. In Study 1, a cross-cultural adaptation of the Work/Life Balance Self-Assessment Scale was conducted, to assess perceptions of balance between work and personal life in a general sample of Brazilian workers (N = 340). Evidence for the validity of the Brazilian version of this instrument was found considering: the three-dimensional structure of the scale, adequate precision of these factors, and relationships among scores on the adapted scale and measures of satisfaction and stress at work. Considering the increase in telework at home (home office), especially during the COVID-19 pandemic, in the other two studies the aim was to understand the impact of organizational variables on perceptions of work-life balance among Brazilian teleworkers. In Study 2, the relationship between conditions of flexibility, autonomy and overtime demands on perceptions of work-life balance among Brazilian teleworkers was examined. Participants who reported the presence of the analyzed target condition and those who reported the absence of the same condition were compared (N = 258). Teleworkers whose work conditions permitted flexibility and autonomy perceived better work-life balance than teleworkers without these conditions. In addition, teleworkers who reported working overtime perceived greater interference between work-personal life and personal life-work than teleworkers who did not face overtime demands. Finally, the objectives of Study 3 were to: (a) analyze the influence of five organizational variables (supportive organizational culture, management style, satisfaction with the manager, peer support, and satisfaction with colleagues) on perceptions of enhancement and of interference between work and personal life involvements, among teleworkers, and (b) based on boundary theory, analyze the role of managers as a mediator (border keeper) between a workplace culture that supports balance, and perceptions of enhancement or of interference between work and personal life involvements, among teleworkers (N = 148). A more supportive workplace culture predicted less work interference in personal life (adjusted R² =.19, p < 0.001), while higher satisfaction with one’s manager predicted perceptions of lower interference of personal life at work (adjusted R² =.04, p < 0.001) as well a more beneficial relationship between work-life involvements (adjusted R² =.12, p < 0.001). The role of the manager, represented by satisfaction with the manager, had a mediating effect on the relationship between supportiveness of the workplace culture and perceptions of work-life balance, partially supporting the concept of border keepers, based on boundary theory. Based on the results of these three studies, theoretical and methodological contributions were made, and evidence was presented indicating the influence of work conditions and organizational factors on perceptions of benefits and of interference in the relationship between work and personal life involvements, among Brazilian teleworkers. The results of Studies 2 and 3 can be used to develop policies and programs that help teleworkers achieve better work-life balance. Considering the influence of the pandemic, however, these results should be confirmed in the post-pandemic context. Longitudinal studies and the inclusion of other informants, in addition to the workers themselves, may also contribute to a better understanding of factors that affect teleworkers’ experiences of work-life balance.
Work-life balance of Brazilian teleworkers
Keywords: Equilíbrio trabalho-vida pessoal; Escala; Recursos humanos; Gestão de pessoas; Bem-estar no trabalho; Work-life balance; Scale; Human resources; People management; Well-being at work; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO TRABALHO E ORGANIZACIONAL::FATORES HUMANOS NO TRABALHO